2000
DOI: 10.1046/j.1468-3083.2000.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lithium carbonate (Li2CO3) on in‐vitro‐cultured normal human skin explants

Abstract: The early morphological changes induced by lithium carbonate, a well-known psoriasis-provoking drug, were studied on cultured skin. Normal human skin from patients undergoing mastectomy was cultured in the presence of 3 mM, 6 mM and 10 mM of Li2CO3 for 4 days. The morphological changes were then evaluated by three observers in a blind manner and their reports were matched and collated. The cultured skin in the presence of Li2CO3 showed cell crowding of keratinocytes in the lower part of the epidermis, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…There was a 20% difference in the amount of apoptotic cells between the control group and the week 1 group. Comparing different substrata, the collagen-embedded explants had much better morphology than the plastic-embedded group, which is also in accordance with other studies [Reaven and Cox, 1965;Flaxman and Harper, 1975;Wolf et al, 2000;Kivinen et al, 2003]. The plastic explant had pronounced degeneration in the epidermis after 7 days.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There was a 20% difference in the amount of apoptotic cells between the control group and the week 1 group. Comparing different substrata, the collagen-embedded explants had much better morphology than the plastic-embedded group, which is also in accordance with other studies [Reaven and Cox, 1965;Flaxman and Harper, 1975;Wolf et al, 2000;Kivinen et al, 2003]. The plastic explant had pronounced degeneration in the epidermis after 7 days.…”
Section: Discussionsupporting
confidence: 90%
“…ECM, cell populations, vasculature, and perhaps some biochemical signals may remain intact in explant cultures. The disadvantage of culturing explants in vitro is the diffi culty in preserving the explants over extended periods of time and the degeneration of the epithelial layer beginning at 72 h in culture [Reaven and Cox, 1965;Flaxman and Harper, 1975;Wolf et al, 2000]. Different systems have been investigated to maintain explants for extended culture periods.…”
Section: Introductionmentioning
confidence: 99%
“…have argued the precise role of proinflammatory cytokines in the production of lithium‐induced psoriasis and suggested two separate mechanisms for the production of psoriatic lesions in patients taking lithium and patients not taking lithium 61 . In vitro studies on human cell culture have demonstrated lithium to play a direct role in epidermal hyperproliferation and indirect role in altering epidermal barrier function and generating signals to the nucleated layer of the epidermis to proliferate in an attempt to restore the barrier, increasing cell turnover, intercellular edema, and vacuolar alteration with function of small cavities in the upper dermis 62 . It was shown that lithium increased intracellular tyrosine phosphorylation in psoriatic T cells compared to control T cells 41 .…”
Section: Mechanism Of Action Of Lithiummentioning
confidence: 99%
“…Other authors, however, have argued about the precise role of pro‐inflammatory cytokines in the production of lithium‐induced psoriasis, and have suggested two separate mechanisms for the production of psoriatic lesions in patients taking or not taking lithium 60 . In vitro studies of cultures of normal human skin with lithium have demonstrated the direct role of lithium in epidermal hyperproliferation, leading to the modification of epidermal barrier function by the production of intercellular edema and vacuolar alteration with the formation of small cavities in the upper dermis 61 . Patients with a positive family history for psoriasis should be carefully evaluated for the potential development of this condition later during the course of treatment 40 .…”
Section: Dermatologic Manifestationsmentioning
confidence: 99%